Evaluating the upgrading of technical courses at two-year colleges NSF's advanced technological education program - Gullickson, Arlen R.; Lawrenz, Frances; Keiser, Nanette (Advances in program evaluation ;, 2004)
The National Science Foundations (NSF) Advanced Technological Education (ATE) program is a diverse and dynamic set of projects intent on improving the USA's technical workforce. This book uses the ATE work as a means to focus on key issues for federally funded projects and all community colleges facing the difficult challenges of staying current and reaching constituents in positive ways. This book brings a wealth of information on key issues for community colleges. Topics addressed include: how to sustain innovative programs; how to develop effective instructional materials; how to promote and maintain collaboration among various institutions including business and industry; how to provide high quality professional development; how to strengthen and improve programs of study; how to recruit and retain diverse students; how to evaluate and use evaluation effectively; and how to engage advisory committees to effectively serve program needs. In developing these topics, the authors drew heavily on previous research and a common set of evaluation studies including site visits at 13 different projects and surveys of more than 100 ATE projects.